2016
DOI: 10.1007/jhep02(2016)004
|View full text |Cite
|
Sign up to set email alerts
|

Chaos in quantum channels

Abstract: Abstract:We study chaos and scrambling in unitary channels by considering their entanglement properties as states. Using out-of-time-order correlation functions to diagnose chaos, we characterize the ability of a channel to process quantum information. We show that the generic decay of such correlators implies that any input subsystem must have near vanishing mutual information with almost all partitions of the output. Additionally, we propose the negativity of the tripartite information of the channel as a ge… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

20
879
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 655 publications
(900 citation statements)
references
References 74 publications
(277 reference statements)
20
879
1
Order By: Relevance
“…Given a boundary region A containing a number of open links of the tensor network, the entanglement entropy of the tensor network in each of the above approaches reproduces an analog of the RT formula (See e.g. [37][38][39][40][41][42][43][44][45][46] for some more recent developments)…”
Section: Jhep11(2017)148mentioning
confidence: 99%
“…Given a boundary region A containing a number of open links of the tensor network, the entanglement entropy of the tensor network in each of the above approaches reproduces an analog of the RT formula (See e.g. [37][38][39][40][41][42][43][44][45][46] for some more recent developments)…”
Section: Jhep11(2017)148mentioning
confidence: 99%
“…This allows us to connect analytically the free UV theory to the interacting and nearly conformal IR theory. Further recent work in this or similar models includes [14,15,16,17,7,18,19]. See also [20,21] for a string motivated model with disorder.…”
Section: Introductionmentioning
confidence: 99%
“…Very importantly, as a characteristic velocity of a chaotic quantum system, v B sets a bound on the speed of the information propagation [1]. In holographic theories, the butterfly effect has extensively been studied in context [5][6][7][8][9][10][11][12][13][14][15][16][17]. In the study of high energy scattering near horizon and information scrambling of black holes it is found that the butterfly effect ubiquitously exists and is signaled by a…”
Section: Introductionmentioning
confidence: 99%